Family development and cohousing (Research, Society and Development, 2022)
Family development must take place from the perspective of processes of alterity, reciprocity and subsidiarity, recognizing relationships as strengths to be developed. The purpose of this article is to elucidate the creation, our common home, as an act of love, in which people, through parenting and work raise sociability and economy so that, based on subsidies, needs and possibilities. Understanding the human being as an agent that enables the necessary praxis for the care of the Common Home has been the purpose for which narrative research has been developed with the aim of developing the anthropological sense that succincts the person as the administrator of the world, for this approach research qualitative and narrative, the documents of the Social Doctrine of the Catholic Church are used, as well as documents that present the family experience. It is concluded that each family is, a concrete gesture to the way the human family lives, the awareness of being the administrators of the cohousing, elevating the human being to the praxis of administration.